La auditoría tributaria y su influencia en las sanciones tributarias de las micro y pequeñas empresas de la región Puno, periodos 2023-2024 - Armuto Quispe, Karen Anait (2025)
The current research focuses on examining how the tax audit impacts the reduction of tax penalties for micro and small businesses in the Puno region. These companies face significant challenges in complying with tax regulations and obligations established by SUNAT, which is attributed to the lack of tax audits that could mitigate tax risks. The central question of this study is: To what extent does the tax audit contribute to reducing tax penalties in micro and small businesses in Puno during the years 2023 and 2024? The objective is to determine the degree of effectiveness of the tax audit in reducing said penalties in the same period. To carry out this research, scientific methods such as descriptive, analytical and deductive methods will be used. This research will be descriptive, non-experimental and will have a quantitative approach; A survey will be applied using a questionnaire validated using Cronbach's Alpha, aimed at a sample of 382 micro and small companies registered in SUNAT, selected through simple random probabilistic sampling from a total population of 58,505 companies in the region.